Decolonization perspectives from now and then - Duara, Prasenjit (London Routledge, 2003)
Decolonization brings together the most cutting-edge thinking by major historians of decolonization, including previously unpublished essays and writings by leaders of decolonizing countries including Ho Chi-Minh and Jawaharlal Nehru. The chapters in this volume present a move away from Western analysis of decolonizaton and instead move towards the angle of vision of the former colonies. This is a ground-breaking study of a subject central to recent global history.
Includes bibliographical references Index.
Keywords: Decolonization, Imperialism. Postcolonialism. Social change